Regulation of c-fos transcription in mouse fibroblasts: identification of DNase I-hypersensitive sites and regulatory upstream sequences. - Renz, M (1985)
In quiescent mouse fibroblasts, the c-fos gene is expressed at very low levels, but is rapidly and transiently inducible by peptide growth factors. In this study, we have identified in quiescent cells five DNase I-hypersensitive sites located -1700, -290, +10, +240 and +700 bp relative to the 5' cap site. After serum stimulation, the distinct nuclease hypersensitive site at position +10 rapidly disappeared, and instead a broad region of DNase I accessibility between positions 0 and +250 occurred. Nucleotide sequence analysis of the 5'-flanking region of the mouse c-fos gene showed that the hypersensitive site around position -290 is located in a region that is highly conserved between mouse and human, and that contains an enhancer-like structure. When the mouse c-fos promoter and 351 bp of 5'-flanking sequences were linked to the bacterial chloramphenicol acetyl transferase (CAT) gene and transfected into NIH3T3 cells efficient, constitutive expression of CAT activity was observed, even in unstimulated, quiescent cells. However, removal of a 256-bp stretch upstream from position -95 completely abolished CAT expression, indicating that sequences within a region of approximately 350 bp upstream from the cap site are indispensable for c-fos transcription. In addition, our findings point to the existence of other sequence elements that exert negative regulation in the absence of growth factor stimulation. Such sites may be found around the growth factor-responsive nuclease hypersensitive sites in the vicinity of the cap site.